Paradigm in the recent management of chronic myocard ischaemia. - Bambang Irawan, Bambang Irawan (Universitas Gadjah Mada, 2005)
Until now coronary heart disease is the number one killer in the world. Angina pectoris is one of the clinical manifestations of coronary heart disease. If there is an insufficient oxygen supply to meet the need ischaemic myocard will happen.Life style changing, drug treatment and operative procedure are applied for the management of pain caused by myocardial ischaemia. According to many big anti-thrombotic trials statin, ACE inhibitor, calcium inhibitor, beta blocker and nitrate are very helpful in the management of chronic coronary artery disease. Myocardial laser revascularization, enhanced external counter pulsation and spinal cord stimulation are alternative procedures in which we can handle it with common management. While conventional therapies are continued to be improved, strategies to increase myocardial circulation by stimulating formation of collateral vessels around the obstructed coronary arteries are also in development. These approaches include angiogenesis, protein transfer, gene therapy and cell therapy. It is hoped that those approaches will safely and effectively applied in the management of chronic coronary artery disease.Â Key words: Coronary heart disease - chronic stable angina - myocardial ischaemia - new approaches